Navigating dual role demands: Self-adjustment as a differential predictor of organizational responsibility and academic achievement among female students in Islamic boarding schools - Anjali Bi Izza Al-Islami; Any Nurhayaty; Sulastri Sulastri (ENLIGHTEN (Jurnal Bimbingan dan Konseling Islam), 2025)
Female students in Islamic boarding schools often experience dual role demands, as they are required to balance intensive organizational responsibilities with sustained academic performance. This study investigates the role of self-adjustment as a psychological factor influencing organizational responsibility and academic achievement among adolescent female students. Employing a quantitative correlational design, the study involved 39 female student leaders (santriwati) serving as administrators of the Student Organization of Pondok Modern Darussalam Gontor Putri Campus 8, selected through purposive sampling. Data were collected using the Self-Adjustment Scale, the Organizational Responsibility Scale, and documented academic achievement scores from report cards. Multiple linear regression analysis was applied to examine the predictive relationships among variables. The findings reveal that self-adjustment significantly predicts organizational responsibility (r = 0.426, p < 0.05), indicating that higher adaptive capacity is associated with stronger organizational engagement and responsibility. However, self-adjustment does not significantly predict academic achievement (r = 0.119, p > 0.05), suggesting that academic performance is more strongly influenced by other factors, such as learning motivation and study strategies. These results highlight the differential role of self-adjustment in managing dual role demands within Islamic boarding school contexts. The study underscores the importance of strengthening adaptive skills through counseling, coaching, and mentoring programs to support female students’ effectiveness in organizational roles without compromising their academic development.